2019
DOI: 10.4269/ajtmh.17-0688
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Anemia in a Birth Cohort in Coastal Kenya: Links to Infection and Nutrition

Abstract: . Anemia is known to impact a child’s growth and development, but not all anemias are caused by iron deficiency, and the CDC and WHO have emphasized investigating other contributors to anemia. This cross-sectional sub-study of a 2012–2016 maternal-child cohort in coastal Kenya evaluated 244 children and found 185 (76%) to have been anemic on at least one time point since birth. At the time of assessment in 2016, evaluation included a complete blood count, nutritional assessment, and testing for para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In choosing to characterize only the non-nutritional causes of stunted growth in this population, child nutritional intake is a confounder that was not examined in this study. We predict that this factor may play a role in the occurrence of stunted growth in this community, given our research group has previously reported a lifetime average blood hemoglobin concentration in the anemic range (< 11 g/dL) in 95% of this pediatric population [10], indicating chronic micronutrient deficiency. Even so, such a high prevalence of anemia in this population is unlikely to explain the observed variation in the occurrence of stunted growth.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In choosing to characterize only the non-nutritional causes of stunted growth in this population, child nutritional intake is a confounder that was not examined in this study. We predict that this factor may play a role in the occurrence of stunted growth in this community, given our research group has previously reported a lifetime average blood hemoglobin concentration in the anemic range (< 11 g/dL) in 95% of this pediatric population [10], indicating chronic micronutrient deficiency. Even so, such a high prevalence of anemia in this population is unlikely to explain the observed variation in the occurrence of stunted growth.…”
Section: Discussionmentioning
confidence: 91%
“…Though inadequate food intake during childhood is one established cause of acute malnutrition and diminished linear growth, chronic malnutrition and stunted growth may also be the result of a variety of other environmental factors. Both childhood exposure to infectious disease and household socioeconomic status (SES) have been demonstrated to correlate with stunted growth [10]. Infant low birth weight, (< 2500 g), which has known links to maternal tobacco use, undernutrition, and anemia, has also been demonstrated to predict stunted growth in childhood, indicating that prenatal exposures may contribute chronic malnutrition [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, although we statistically controlled for differences in socioeconomic status, we acknowledge that unrecognized confounders or contributors to anemia may exist and explain some of the apparent effects of HIV exposure on hemoglobin levels. These include parasitaemia 33 , 34 and lingering effects of, or ongoing exposure to, antiretroviral drugs, 35 , 36 and additional measures of socioeconomic status. Additionally, because the children invited to participate in this study were not randomly sampled from the population of children in Eldoret, it is not possible to say what the true prevalence of anemia is in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Helminths can exacerbate malnutrition by a variety of different mechanisms, including causing reduced appetite and food intake, provoking blood loss resulting in anaemia, reducing lactase activity, causing the malabsorption of vitamin A and fat and, in the case of heavy parasitic burdens, directly causing poor digestion and bowel obstruction 109,117,118 . In rats, infection with the roundworm N. brasiliensis directly impaired glucose absorption in intestinal epithelial cells 119 .…”
Section: Child Growth Undernutrition and Stuntingmentioning
confidence: 99%